2010 43rd Hawaii International Conference on System Sciences 2010
DOI: 10.1109/hicss.2010.316
|View full text |Cite
|
Sign up to set email alerts
|

Reorganizing Projects through Enterprise System: Emerging Role of Enterprise System in Radical Organizational Change

Abstract: In this paper we analyze the role of Enterprise System (ES) in shaping a company's transformation process by conducting an in-depth case study in a large European high-tech company. Although there are previous studies concerning organizational transformation and ES implementation process, the role of ES as an instrument for de-institutionalization is not well understood. By drawing on the framework of neo-institutional theory we seek to understand how ES facilitates discarding of the old ways of doing things a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Devadoss and Pan, 2007; Mattia, 2011; Orlikowski, 1996); how established beliefs, attitudes and behaviors are created and destroyed in the change process of IT and organizations (e.g. Avgerou, 2000; Mattila et al , 2010; Wamba and Chatfield, 2009); how organizational culture enables, resists or is altered by IT-enabled transformational change (e.g. Fernández et al , 2010; Massaro, 1993; Philip and McKeown, 2004); and what capabilities are needed to realize business value from transformational processes (e.g.…”
Section: Review Resultsmentioning
confidence: 99%
“…Devadoss and Pan, 2007; Mattia, 2011; Orlikowski, 1996); how established beliefs, attitudes and behaviors are created and destroyed in the change process of IT and organizations (e.g. Avgerou, 2000; Mattila et al , 2010; Wamba and Chatfield, 2009); how organizational culture enables, resists or is altered by IT-enabled transformational change (e.g. Fernández et al , 2010; Massaro, 1993; Philip and McKeown, 2004); and what capabilities are needed to realize business value from transformational processes (e.g.…”
Section: Review Resultsmentioning
confidence: 99%
“…They found that management accountants were restricted to their traditional role of merely collecting cost information for decision-making. Mattila et al (2009) drew on the neo-institutional theory to investigate the implementation of an enterprise systems (ES) in a company operating in a technology sector. They investigated how the company responded to market and institutional pressures and highlighted the role of the ES during the organizational change process.…”
Section: Literature Reviewmentioning
confidence: 99%